Cross-sectional associations between patterns of cultural engagement and indicators of biological dysregulation - Emma S. Walker; Daisy Fancourt; Meena Kumari; Anne McMunn (Annals of Human Biology)
Background Research has shown that cultural activities may bring about improved health. However, large-scale quantitative analyses on cultural engagement and biomarkers are lacking to date. As a result, the mechanisms through which cultural activities may be associated with health are unclear.Aim Test quantitative associations between cultural engagement pattern (including active and passive engagement in arts, sports, and heritage activities) and indicators of biological dysregulation in a large dataset.Subjects and methods Understanding Society data were used to conduct cross-sectional linear regression analyses between a data-driven latent class model of cultural engagement and indicators of anthropometric, cardiovascular, metabolic, immune, and neuroendocrine function. Analyses were adjusted for age, gender, ethnicity, childcare responsibility, urbanicity, leisure time satisfaction, capacity-related factors, socioeconomic position, social and economic capital indicators, physical activity, and medication use.Results More culturally participants had better indicators of biological health, such as lower waist circumference and fibrinogen blood concentration. Specific associations between cultural engagement pattern and the different biological outcomes were also observed. The associations were explained in part by correlated factors (accounting for around half of the association).Conclusions Cultural engagement is cross-sectionally associated with biomarkers, although the characteristics of people who engage with culture are an important consideration when interpreting these findings.